2002
DOI: 10.1016/s0736-0266(01)00175-9
|View full text |Cite
|
Sign up to set email alerts
|

High frequency distraction improves tissue adaptation during leg lengthening in humans

Abstract: The present study investigates the effect of distraction frequency on the development of tensile force in the tissues during lengthening. Two patients with bilateral Ilizarov leg lengthening underwent distraction with high frequency in one leg and low frequency in the other. The clinical situation represented a unique model for investigating the effect of distraction frequency, as each individual served as its own control. Both patients had double level lengthening. Distraction frequency at the proximal length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…However, the reports on distraction and tension rate have been inconsistent. While some studies have shown that healing quality does not depend on distraction rate (Augat et al, 2001, Hente et al, 2004), others have data which indicate the opposite (Isaksson et al, 2007, Aarnes et al, 2002, Ilizarov, 1989). One possible explanation for this inconsistency, might be that the tissues and cells involved in bone healing are more sensitive to compression rather than tension.…”
Section: Mechanical Strain and Pressurementioning
confidence: 99%
“…However, the reports on distraction and tension rate have been inconsistent. While some studies have shown that healing quality does not depend on distraction rate (Augat et al, 2001, Hente et al, 2004), others have data which indicate the opposite (Isaksson et al, 2007, Aarnes et al, 2002, Ilizarov, 1989). One possible explanation for this inconsistency, might be that the tissues and cells involved in bone healing are more sensitive to compression rather than tension.…”
Section: Mechanical Strain and Pressurementioning
confidence: 99%
“…At the same time, sustained application of mechanical force can sometimes repair diseased tissues. For instance, in a process referred to as distraction osteogenesis, gradual traction on bones is used to enhance osteogenesis for the treatment of skeletal deformities in dogs and humans (Ilizarov, 1989a;Ilizarov, 1989b;Aarnes et al, 2002). Similarly, constant stretching of the intestines leads to an increase in intestinal length in rats (Park et al, 2004) and stretching induces regeneration and lengthening of the esophagus in human infants with esophageal atresia (Foker et al, 1997).…”
Section: Deregulation Of Mechanosensitive Transcriptional Control Andmentioning
confidence: 99%
“…The third is the consolidation phase, during which there is no distraction, which finally leads to bony union. The rate of bone formation during DO is directly related to the distraction rate (Ilizarov, 1989b;Li et al, 1999Li et al, , 2000, frequency (Aarnes et al, 2002;Ilizarov, 1989b;Mizuta et al, 2003) and the strain/stress generated in the distraction gap (Li et al, 1997(Li et al, , 1999. Meyer et al (2001a) showed that the magnitude of distraction-generated mechanical tension directly influenced the phenotypic differentiation of the cells within the distraction gap.…”
Section: Introductionmentioning
confidence: 99%